Application of the Syntax Learning Model Based on the Umbrella Model to Improve Cognitive Learning Outcomes in Volleyball Material. - Endriani, Dewi; Gultom, Syamsul; Daulay, Basyaruddin; Destya, Muhammad Reza (Journal La Edusci, 2025)
This study aims to apply a syntax-based learning model using the umbrella model approach to enhance students’ cognitive learning outcomes in volleyball material. The research was conducted through two stages: a limited trial and an expanded trial. The limited trial was carried out in Class E, Semester II, involving 20 students. After revisions and improvements, the expanded trial was conducted in Class A, Semester II, with 40 students. Both trials used a one-group pretest-posttest design, and data analysis employed the Shapiro-Wilk test using SPSS Version 25. The results showed that the control class obtained an average cognitive score of 30.03 (47.50%) with a standard deviation of 1.54, while the experimental class achieved an average score of 35.02 (50.00%) with a standard deviation of 1.714. Statistical testing at a 95% confidence level revealed a significance value of 0.00 (<0.05), indicating that Ho was rejected. This means there was a significant difference between students taught using conventional methods and those taught using the syntax learning model based on the umbrella model. Thus, it can be concluded that the application of the umbrella model-based syntax learning model effectively improves students’ cognitive learning outcomes in volleyball material. The model encourages active learning, structured understanding, and better mastery of cognitive concepts compared to traditional teaching methods.